2023
DOI: 10.1002/joe.22198
|View full text |Cite
|
Sign up to set email alerts
|

Person‐organization fit and turnover intention: The mediating role of need‐supply fit and demand‐ability fit

Abstract: The Great Resignation indicates that many organizations are grappling with the human resource challenge of staff retention and turnover, in which fit plays a prominent role. Extrapolating the role of fit, this study investigates the effects of person‐organization fit, need‐supply fit, and demand‐ability fit on turnover intention. The study also investigates whether need‐supply fit and demand‐ability fit mediates the effect of person‐organization fit on turnover intention. The data gathered from 250 full‐time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…At a time when one of the biggest problems facing organizations is high employee turnover (Reiche 2008;Martins et al 2023), leading to substantial financial losses for organizations, as the loss of a highly competent employee will affect the organization's reputation, profitability, and performance (Kumar et al 2021;Kakar et al 2023), this study has confirmed that if an organization wants to retain its best employees, it must invest in developing their skills in order to boost their emotional commitment and reduce their intentions to leave (Koster et al 2011;Nguyen et al 2020;Rodrigues et al 2019). It was also concluded that, of all the development practices studied, individualized support acts as the greatest reducer of intentions to leave, results that are maintained when analyzing the effect by generation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a time when one of the biggest problems facing organizations is high employee turnover (Reiche 2008;Martins et al 2023), leading to substantial financial losses for organizations, as the loss of a highly competent employee will affect the organization's reputation, profitability, and performance (Kumar et al 2021;Kakar et al 2023), this study has confirmed that if an organization wants to retain its best employees, it must invest in developing their skills in order to boost their emotional commitment and reduce their intentions to leave (Koster et al 2011;Nguyen et al 2020;Rodrigues et al 2019). It was also concluded that, of all the development practices studied, individualized support acts as the greatest reducer of intentions to leave, results that are maintained when analyzing the effect by generation.…”
Section: Discussionmentioning
confidence: 99%
“…This response can be interpreted through the theory of planned behavior, since behavioral intentions are causal antecedents of behavior (Ajzen 2012). In the view of Kakar et al (2023), when an employee intends to leave the organization where they work, this is the final step towards leaving the organization, whether by resignation or through termination. Despite the existence of authors who question this relationship (Cohen et al 2016), this is one of the reasons why this construct has been widely studied, especially when one of the current objectives of organizations is to retain the best employees (Long et al 2012;Park and Shaw 2013).…”
Section: Turnover Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…High turnover intention (TOI) inhibited primary business goals and resulted in substantial organisational losses ( Kumar et al, 2021 ). The loss of a highly competent employee affects organisational reputation, profitability and performance ( Muzaffar and Javed, 2021 ; Kakar et al, 2023 ), commitment and overall vision ( Kumar et al, 2021 ). Additionally, the loss of competent academicians could negatively affect the reputation of a university and the quality of work produced.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of the research has overlooked the impact of factors that are beyond the control of the organisation ( Kakar et al, 2023 ). For instance, job opportunity (JBO) is an external aspect that is potentially crucial in comprehending employees’ attitudes and behaviours ( Kakar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%